Chico Mendes, the rubber tappers and the Indians: reimagining conservation and development in the Amazon - Schwartzman, Stephan (Desenvolvimento e Meio Ambiente, 2018)
In the mid-1970’s rubber tapper leaders Chico Mendes and Wilson Pinheiro reformulated strategic objectives of the rubber tappers’ movement, from protesting and denouncing violent dispossession of families and deforestation to defending rubber tappers’ forest territories and diversified land use. This strategic turn laid the basis for the rubber tappers’ transformation from a solely class-based union movement to one that incorporates a specific cultural identity associated with land and resource uses defined as opposed to the government-sponsored socio-environmentally destructive development model. The rubber tappers’ conceptual transformation of “extractivism”, from an archaic, outdated and primitive economic activity into an alternative for a modern, sustainable development model, based in their distinct culture, mirrored and paralleled the emergence of identity-based social movements globally. It also mirrored the re-emergence of “submerged” indigenous ethnicities and subsequent “ethnogenesis” of allegedly extinct or forgotten indigenous peoples, in both cases contrary to the assumptions and predictions of both policy and some anthropological theory. The rubber tappers’ definition of extractive reserves as collective land rights – and access to technology, social services and markets on terms in some measure controlled by the communities – in exchange for environmental and forest protection enabled significant territorial gains (parallel to indigenous territories), as well as proliferation of extractive reserve analogues in both environmental and land reform policy. Alliances with indigenous peoples and environmentalists were central to the development of this vision. The model of collective rights, with access to technology, services and markets could have very broad applicability for poor populations globally, in light of climate change and other environmental crises, if at-scale incentives for climate change and other environmental mitigation can be created.